A New Compact Size Microstrip Patch Antenna with Irregular Slots for Handheld GPS Application - Jawad K. Ali (Engineering and Technology Journal, 2008)
A new reduced size single probe fed microstrip patch antenna with irregular slitshas been presented to be used as a receiving antenna for Global Positioning Systems(GPS) integrated with cellular handheld mobile wireless systems. The proposed design isbased on the nearly square microstrip patch antenna with two pairs of orthogonal slitscut from the edge. It has been found that this antenna offers further reduction in sizewith good radiation properties required for GPS system. The resulting circularpolarization bandwidth (with axial ratio ≤ 3 dB) has been found to meet that required forthis application. The proposed antenna possesses an average gain of 4.5 dB overall theGPS L1 operation.